Linking Rural and Urban Circular Economies through Reuse and Repair. Issue 2 (20th November 2019) - Berry, Brieanne; Isenhour, Cindy
Abstract: Increasing resource scarcity and what has been called "the end of cheap nature" are prompting policymakers and scholars to foster more circular economies to reduce waste and lengthen the lifespan of material goods. Our essay critically examines the political and economic relationships between urban and rural geographies in the context of secondhand economies. Practices of bartering, swapping, selling, and repairing used goods have long been important to rural people and places, but the increasing commodification of discards risks upending rural livelihoods and ways of being as goods move toward urban centers. We explore the relationship between rural and urban reuse economies and suggest how future scholars of rural North America might contribute to strengthening and supporting localized reuse practices.